The Impact of Credit Rating Adjustments on Bond Spreads: Evidence from China - Kurbonov, Sinbad; Nasriddinov, Bobur; Mulbah, Kessellie Traore (European Scientific Journal, ESJ, 2024)
Given the critical role of credit ratings in signaling issuer creditworthiness and influencing investor behavior, this paper aims to elucidate how adjustments in these ratings affect bond market spreads. Utilizing a comprehensive dataset spanning from 2016 to 2022, this research focuses on the Chinese bond market. Through regression analysis and heterogeneity tests, the findings reveal that credit rating adjustments significantly influence bond spreads, with upgrades narrowing spreads and downgrades widening them. Additionally, adjustments related to external support and firm performance also affect spreads, highlighting the importance of managing credit ratings for issuers. Overall, this study offers insights for investors, issuers, regulators, and academics, providing a better understanding of the dynamics between credit rating adjustments and bond pricing in China’s bond market, with implications for financial stability and economic development.